Electoral effects of intergovernmental fiscal transfers: an application to local elections in the province of Cordoba, 1995-2011 - Freille, Sebastián (2014)
We examine the impact of descentralized public policy in the form of inter-governmental fi scal transfers on local election outcomes –the probability of reelection. We assemble a new and unique dataset recording every local ex-ecutive election in the period 1995-2011 and examine the electoral effect of various types of intergovernmental fi scal transfers. We fi nd that the odds of reelecting local incumbents are increasing in the incumbency dummies for both major parties. Local governments which receive a positive discretion-ary transfer from the provincial government have also associated higher odds of being reelected. The probability of reelection is also increasing in the difference in the vote share between the winner and the runner up in the previous election. Finally we fi nd evidence that the amount of discretionary transfers per capita affect positively the probability of reelection only in those governments aligned with the provincial government. Our results are robust to controlling for other potential explanatory variables.